2009
DOI: 10.3109/13625180903340584
|View full text |Cite
|
Sign up to set email alerts
|

Improved access increases postpartum uptake of contraceptive implants among HIV-positive women in Rwanda

Abstract: When access to LARC was provided, a substantial number of HIV-positive women started using hormonal implants, but not IUDs, in the postpartum period. HIV and FP services should consider improving access to implants to reduce the number of unintended pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 15 publications
1
31
1
Order By: Relevance
“…The proportion of women wanting to limit fertility is comparable to previously reported figures of 50-90% among women living with HIV or with HIV-positive partners [9, 10]. The very low proportion of women using LARC nationwide, <2% in Rwanda and <0.5% in Zambia [19, 21], confirms a substantial unmet need for long-acting methods.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The proportion of women wanting to limit fertility is comparable to previously reported figures of 50-90% among women living with HIV or with HIV-positive partners [9, 10]. The very low proportion of women using LARC nationwide, <2% in Rwanda and <0.5% in Zambia [19, 21], confirms a substantial unmet need for long-acting methods.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have demonstrated that increasing access to LARC methods improves their uptake among HIV-positive women. In Rwanda, providing information and access to hormonal contraceptives resulted in increased use among both HIV-positive and HIV-negative women [8], and when access to LARC was provided on-site, a substantial portion of HIV-positive women requested hormonal implants postpartum [9]. In Zambia, improving access to non-barrier methods among HIV-concordant-positive and HIV-discordant couples already using condoms increased dual-method use three-fold [10], and a video-based intervention resulted in significantly increased uptake of LARC in discordant and concordant HIV-positive couples [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among studies of adult HIV-seropositive women, the majority have been conducted in international settings, primarily in Africa [104110], with few studies from the USA [111]. These reports highlight the importance of access to health care [104, 105], reporting women's concerns about contraceptive side effects [108] or potential interactions with ARVs [108], convenience of barrier contraceptive methods [104, 105, 111], and desire to have children [107109] as determinants of contraceptive method use in women living with HIV [104]. Additionally, contraceptive use may differ by partner type; for instance, among a cohort of French women living with HIV, contraceptive use was more prevalent among women reporting recent sexual encounters with casual partners [112].…”
Section: Factors That Influence Contraceptive Choice May Impact Hiv Riskmentioning
confidence: 99%
“…Exposure to a video highlighting IUD and contraceptive implants was associated with greater choice of those methods. Another study conducted in Rwanda showed high uptake of implants when this method was made available to postpartum PMTCT clients [18]. …”
Section: Introductionmentioning
confidence: 99%